1985
DOI: 10.1002/ana.410180407
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional analysis of T cells cloned directly from the blood and cerebrospinal fluid of patients with multiple sclerosis

Abstract: A single-cell cloning technique was used to analyze both phenotype and function of individual T cells in patients with multiple sclerosis (MS). Blood and cerebrospinal fluid (CSF) lymphocytes were plated at 1 cell per well, stimulated with phytohemagglutinin followed by interleukin 2, and expanded to 3 X 10(6) cells per "clone." More than 90% of the T8 clones generated from patients with MS and controls in both blood and CSF were cytotoxic precursors. There was also a slight decrease in cytotoxic T4 clones in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…In this study, cloning efficiency was almost equivalent to that in previous studies (Fleischer and Kreth 1983 ;Fleischer et al 1984 ;Martin et al 1988Martin et al , 1989, although higher cloning efficiency is also reported (Hafler et al 1985). According to the method of Moretta et al (1983), the number of viable lymphocytes after 14-20 days in culture ranged between 5 X 104 and 3 X 105 per microwell, and cloning efficiency from PBL reached near 50%.…”
Section: Production Of Lt/ Tnfa and Ifn-y In T -Cell Linessupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, cloning efficiency was almost equivalent to that in previous studies (Fleischer and Kreth 1983 ;Fleischer et al 1984 ;Martin et al 1988Martin et al , 1989, although higher cloning efficiency is also reported (Hafler et al 1985). According to the method of Moretta et al (1983), the number of viable lymphocytes after 14-20 days in culture ranged between 5 X 104 and 3 X 105 per microwell, and cloning efficiency from PBL reached near 50%.…”
Section: Production Of Lt/ Tnfa and Ifn-y In T -Cell Linessupporting
confidence: 78%
“…Since CD4+ and CD8+T-cells would be almost equally expanded, dependent upon their proportion in whole mononuclear cell preparation (Fleischer and Kreth 1983;Hafler et al 1985), it was rather interesting that CD4+CDw29+T cells could be easily expanded in HAM. This may indicate that CD4+CDw29+, gag+T cells are present more frequently than other cell types or this type of T cells proliferate more easily.…”
Section: Production Of Lt/ Tnfa and Ifn-y In T -Cell Linesmentioning
confidence: 99%
“…Recently we have shown (Rotteveel et al, 1988) that during 20 weeks of culture CD4"'" cytotoxic clones consistently lysed target cells in the presence of anti-CD3 MoAb, The non-cytotoxic CD4+ clones did not acquire this cytotoxic activity in that period of time. The cytotoxic capacity ofT cell clones derived from the CSF has also been analysed by other investigators (Hafler et al, 1985a;Weber et al, 1987), Weber et al (1987) found an increased percentage of T cell clones with lectin-dependent cytotoxic capacity derived from the CSF; however, most of these clones also displayed NK activity, Hafler et al (1985a) did not find statistically significant diflerences in the relative number of cytotoxic cells in the CSF and blood.…”
Section: Discussionmentioning
confidence: 82%
“…Single-cell subclones were generated from the PBMC culture by limiting dilution as described. 55 Briefly, 14 days after the previous stimulation, puromycin-resistant cells were seeded at one cell per well of a V-bottom 96-well plate in the presence of PHA, feeder cells and 100 U/ml IL-7. Wells were fed at 3-4 day intervals with medium containing IL-7.…”
Section: Stable Vector Transfer Into Primary T Lymphocytesmentioning
confidence: 99%